Digital Economy Transformation Stock Warehouse PT. Terminal Petikemas Surabaya - Mudayat Mudayat; Meyti Hanna Ester Kalangi; Soedarmanto (Enrichment : Journal of Management, 2022)
Archives stored in digital form can be in the form of images, sound, video, writing or others that can be used as data in binary form, can be processed in computer programs and stored in digital data storage media. Digital transformation of the electronic filing system at the PT. Terminal Petikemas Surabaya using the Maximo System, which is a software application released by IBM where the Maximo function is to manage or it can also be said about time and care for an asset, so that it can work and work as it should, cost efficiency, effectiveness and optimize performance of the asset.